2018
DOI: 10.1021/acs.jmedchem.7b01653
|View full text |Cite
|
Sign up to set email alerts
|

Progress in the Development of Preventative Drugs for Cisplatin-Induced Hearing Loss

Abstract: Cisplatin is a highly effective treatment for malignant cancers and has become a cornerstone in chemotherapeutic regimens. Unfortunately, its use in the clinic is often coupled with a high incidence of severe hearing loss. Over the past few decades, enormous effort has been put forth to find protective agents that selectively protect against the ototoxic side effects of cisplatin and not interfere with its antitumoral activity. Many therapies have been successful in preclinical work, but only a few have shown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
74
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(77 citation statements)
references
References 75 publications
(228 reference statements)
1
74
0
2
Order By: Relevance
“…Pharmacologic blockade of this transporter protects against cisplatin ototoxicity. 21 Mechanotransduction (MET) channels may be involved in the uptake of cisplatin. Inhibition of MET channels protects against cisplatin-induced damage to hair cells in zebrafish, and zebrafish mutants lacking these channels were shown to be resistant to cisplatin-induced cell death.…”
Section: Uptake Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pharmacologic blockade of this transporter protects against cisplatin ototoxicity. 21 Mechanotransduction (MET) channels may be involved in the uptake of cisplatin. Inhibition of MET channels protects against cisplatin-induced damage to hair cells in zebrafish, and zebrafish mutants lacking these channels were shown to be resistant to cisplatin-induced cell death.…”
Section: Uptake Mechanismsmentioning
confidence: 99%
“…Inhibition of MET channels protects against cisplatin-induced damage to hair cells in zebrafish, and zebrafish mutants lacking these channels were shown to be resistant to cisplatin-induced cell death. 21…”
Section: Uptake Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, multiple lines of evidences suggest antioxidants ameliorate cisplatin‐induced side effects (gastrointestinal symptoms such as abdominal discomfort, vomiting, delayed gastric emptying, and gastric distension) and enhanced the antioxidant defense systems . Many previous studies have reported that the mechanisms of D‐methionine protect against cisplatin‐induced toxicities are closely related to its antioxidant effect, protect the endogenous antioxidant system in the body, and reduce oxidative stress . Recent studies in our laboratory indicate that D‐methionine provides protection against cisplatin‐induced intestinal damage through the antioxidative and anti‐inflammatory effects of D‐methionine .…”
Section: Discussionmentioning
confidence: 93%
“…D‐methionine serves as an antioxidant against cisplatin‐induced ototoxicity by protecting the endogenous antioxidant system in the body and forming inactive complexes with cisplatin . In addition, D‐methionine exhibits a variety of actions, not only providing protection against radiation but also providing cytoprotection, nephroprotection, neuroprotection, and weight loss protection .…”
Section: Introductionmentioning
confidence: 99%